Diseño y construcción de una valla inteligente accionada mediante una tarjeta de Banda Magnética para el acceso al parqueadero del bloque "B" en La Universidad Técnica de Cotopaxi, extensión La Maná 2016 - Sigcha Zambrano, José Danilo (2017)
The present project seeks the design and construction of a smart fence powered by a magnetic stripe card f or access to the parking lot of Block B, the construction of the prototype has the purpose of controlling an automated vehicular access system by means of control equipment, Control and registration. The elements used in the design of the control system provide the same operation as an actual vehicle control system. The implementation of the mechanical, electrical and control elements in the prototype are selected within the specified operating characteristics. The electrical elements are relatively low power, the elements of the mechanical transmission system are smaller than those used in a real access control but have the same applications; while the control system employs proximity sensors and the magnetic stripe reader that is used to control vehicular and pedestrian access systems. The construction and location of the prototype elements made to scale are based on the bi-directional double access control system. The tests performed give the expected result, in which when activating the card reader the main circuit is generated generating the lifting of the fence and through the design of the control circuit and the proximity sensors, the fence will only return to its initial state once the vehicle has fully circulated. Finally within the project details the correct maintenance of each of the elements of the prototype as well as the equipment of a real vehicular access control and in this way to avoid possible damage and unnecessary equipment stoppage.